2010
DOI: 10.1242/jeb.039594
|View full text |Cite
|
Sign up to set email alerts
|

γ-Amino butyric acid (GABA) release in the ciliated protozoonParameciumoccurs by neuronal-like exocytosis

Abstract: SUMMARYParamecium primaurelia expresses a significant amount of -amino butyric acid (GABA). Paramecia possess both glutamate decarboxylase (GAD)-like and vesicular GABA transporter (vGAT)-like proteins, indicating the ability to synthesize GABA from glutamate and to transport GABA into vesicles. Using antibodies raised against mammalian GAD and vGAT, bands with an apparent molecular weight of about 67kDa and 57kDa were detected. The presence of these bands indicated a similarity between the proteins in Para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 62 publications
2
6
0
Order By: Relevance
“…Accordingly, in the present study, whole-mount IHC revealed the close association of GABA-IR with the basal body of the cilium. A similar pattern of GABA distribution was reported on the ciliated surface of Paramecium (Ramoino et al, 2010). In the rat oviduct in particular, GABA was seen in the cytoplasm of the tubal epithelium along with the ciliated apical surface (Erdö et al, 1986), which is consistent with the present observation of GABA-IR in the cytoplasm of the blastocoelar cells.…”
Section: Developmental Organization Of the Gabaergic Systemsupporting
confidence: 91%
See 1 more Smart Citation
“…Accordingly, in the present study, whole-mount IHC revealed the close association of GABA-IR with the basal body of the cilium. A similar pattern of GABA distribution was reported on the ciliated surface of Paramecium (Ramoino et al, 2010). In the rat oviduct in particular, GABA was seen in the cytoplasm of the tubal epithelium along with the ciliated apical surface (Erdö et al, 1986), which is consistent with the present observation of GABA-IR in the cytoplasm of the blastocoelar cells.…”
Section: Developmental Organization Of the Gabaergic Systemsupporting
confidence: 91%
“…Although the mechanism by which GABA in the cytoplasm is transported to the basal bodies of cilia was not addressed in the present study, synthesized GABA may be taken up into vesicles in the cytoplasm and then localized to the basal bodies, as has been reported in Paramecium (Ramoino et al, 2010). This is supported by the prediction of the presence of GABA transporter in sea urchin by SpBase (Sp-Gat_2; SPU_000076, etc.).…”
Section: Developmental Organization Of the Gabaergic Systemsupporting
confidence: 77%
“…GABA also seems to play a role in cell communication in P. primaurelia ; this free‐living unicellular organism has GABA A and GABA B receptors, and its capability to synthesize and release GABA into the environment has been demonstrated (Ramoino et al. , , ). In addition, GABA metabolism through partial or complete GABA shunts were described in both, T. gondii and P. falciparum (MacRae et al.…”
Section: Discussionmentioning
confidence: 99%
“…Glutamate in turn is amidated to form glutamine by a glutamine synthetase and transported back to the presynaptic neuron, where it is converted into GABA, completing the glutamate/GABA-glutamine cycle. In addition to its very well-described presence in a variety of organisms, this pathway has recently been described in some protozoan species, such as Paramecium primaurelia and Entoameba invadens (Jeelani et al 2012;Ramoino et al 2010), Toxoplasma gondii (MacRae et al 2012), and Plasmodium falciparum (MacRae et al 2012;Teng et al 2009), where it participates in processes such as intercellular signaling and tropism. Despite its intrinsic interest and broad distribution in the "tree of life", intracellular GABA has not yet been reported for any trypanosomatid.…”
mentioning
confidence: 99%
“…Furthermore, they can be cultured in the laboratory under conditions very similar to those in nature, making their response more reliable than that of animal-cell cultures cultured in artificial conditions (Delmonte Corrado et al, 2006). Finally, it is important to emphasise how in protozoa, the identification of molecules responsible for neurotransmission in metazoan, such as those belonging to the GABAergic system in Paramecium primaurelia (Ramoino et al, 2010) and Dictyostelium discoideum (Anjard & Loomis 2006), to the nitergic system in Paramecium primaurelia (Amaroli et al, 2010), and to the cholinergic system in Paramecium primaurelia, Dictyostelium discoideum, Euplotes crassus (Delmonte Corrado et al,1999;Amaroli et al 2003;Trielli et al, 2007), with characteristics similar to those of the vertebrates, has opened the way to their use in neurotoxicological studies. The genomal sequencing of several protozoa (Dessen et al 2001;Turkewitz et al, 2002;Eichinger et al, 2005), has demonstrated that they have conserved gene sequences compared to human genome and this has stimulated the interest of the scientific community in their use in field studies on human health, as in the case of Dictyostelium discoideum included in the eight alternative models to be used instead of vertebrates in human health studies in the USA (Williams et al, 2006).…”
Section: Introductionmentioning
confidence: 99%